'Letting the right one in': Provider contexts for recruitment to initial teacher education in the United Kingdom. (November 2016) - Davies, Peter; Connolly, Mark; Nelson, James; Hulme, Moira; Kirkman, John; Greenway, Celia
Abstract: We exploit policy differences within the UK to investigate provider context and recruitment to initial teacher education (ITE). We identify three dimensions of variation: conceptions of professionalism, universal or context specific preparation and costs and benefits to providers. University-led ITE programmes used similar criteria and processes in each jurisdiction, but there were differences between university-led and school-led recruitment. Our study suggests that the current shortfall in recruitment to ITE in England may be a product of the contextual constraints which schools experience. It also suggests that school-led recruitment may tend to emphasise short-term and school-specific needs. Highlights: A model of relationships between context and providers' recruitment to ITE. HE recruitment criteria and processes similar in 4 UK jurisdictions. School-led recruitment to ITE emphasising 'classroom readiness' and school needs. Costs and benefits to providers the main source of difference in recruitment.